Tian Mimi Song Analysis Arrangement Dyfan Alvin - Yonatan Kristian Rishak (Universitas Negeri Surabaya, 2020)
It was one of the branches of musical science for exploration for its creators. However, many people do not understand how the arrangement must be worked out often by forgetting and paying no attention to the structure and aspects of the arrangements to be fulfilled. Therefore, researchers picked up one type of Chinese pop song, tian Mimi. The result of the arrangements from a surabaya musician Dyfan Alvin. Researchers use several theories - the proposed theory of analysis, structure, and elements. Researchers are also providing a qualitative, descriptive approach with interviews, observation, and data gathering.It was discovered that the tian Mimi's song arranger leads to